First-principles study of Li-doped planar g-C3N5 as reversible H2 storage material - Chen, Xihao; Liu, Zonghang; Cheng, Jiang; Li, Jiwen; Guo, Donglin; Zhang, Liang; Niu, Xianghong; Wang, Ning; Wang, Guangzhao; Gao, Peng (Frontiers in Chemistry, 2023)
Under the background of energy crisis, hydrogen owns the advantage of high combustion and shows considerable environment friendliness; however, to fully utilize this novel resource, the major hurdle lies in its delivery and storage. The development of the in-depth yet systematical methodology for two-dimensional (2D) storage media evaluation still remains to be challenging for computational scientists. In this study, we tried our proposed evaluation protocol on a 2D material, g-C 3 N 5 , and its hydrogen storage performance was characterized; and with addition of Li atoms, the changes of its electronical and structural properties were detected. First-principles simulations were